An often-overlooked factor in pelvicpain: Pelvic congestion syndrome - Fatma Devran (Journal of Gynecological Research and Obstetrics - Peertechz Publications, 2019)
Chronic pelvic pain (CPP) is defined as intermittent or persistent pain not associated with pregnancy, menstruation or coitus, which is localized in the abdomen or pelvis lasting at least three to six months. It is a common complaint with a prevalence ranging from 2.1% to 24% [1]. Pelvic congestion syndrome (PCS) is a syndrome associated with pelvic varices causing CPP and more frequently seen in women in the reproductive period. However, this syndrome should not be ignored in the diagnosis for women with pelvic pain in the postmenopausal period as in the patient presented herein.